Non-invasive Diagnosis and Prognosis Values of 3D Pseudocontinuous Arterial Spin Labeling and Optical Coherence Tomography Angiography in Proliferative Diabetic Retinopathy - Hou, Yanli; Song, Shuai; Sun, Jiao; Wang, Huihui; Wang, Yanling; Wang, Zhenchang; Li, Jing; Li, Hongyang (Frontiers in Medicine, 2021)
Background: 3D Pseudocontinuous Arterial Spin Labeling (3D-PCASL) MRI and optical coherence tomography angiography (OCTA) have been applied to detect ocular blood flow (BF). We aim to characterize the ocular BF in diabetic retinopathy (DR) using 3D-PCASL and OCTA, to discuss the relationship between ocular and cerebral BF, and to evaluate their potential utility to assess the severity of DR. Methods: A total of 66 participants (132 eyes) were included. Seventy-two eyes were classified in the proliferative diabetic retinopathy (PDR) group, and 60 were in the nonproliferative diabetic retinopathy NPDR group. Ocular and cerebral BF values were detected by 3D-PCASL using a 3.0T MRI scanner with two post-labeling delays (PLDs). Vessel density (VD) / perfusion density (PD) of the macular or peripapillary area were detected by OCTA. Parameters and clinical characteristics were compared between the PDR and NPDR eyes utilizing two-sample t-tests and chi-square tests. Spearman’s rank correlation analysis, logistic regression analysis, and receiver operating characteristic curves (ROC) analyses were performed to evaluate the factors’ role in DR severity. Results: The perfusions of the retinal/choroidal plexus (RCP), optic nerve head (ONH)/optic nerve (ON) and VD/PD of macular/peripapillary area in the PDR group were significantly lower compared to the NPDR group (p<0.05). They were protective factors for PDR [ORs = 0.842 for RCP (1.5s PLD), 0.910 for ONH (1.5s PLD), 0.905 for ON (both 1.5sPLD and 2.5sPLD), 0.707 for macular VD, 0.652 for peripapillary VD, p<0.05 respectively]. Ocular BF had a positive correlation with BF of the occipital lobe (OL) and temporal lobe (TL) in the cerebrum. The BF of RCP (lower than 7.825 mL/min/100 g at 1.5sPLD) indicated PDR [areas under the curve (AUCs)= 0.682, 95% CI: 0.588–0.777, sensitivity:70.7% specifificity:63.9%]. The AUC of RCP (PLD=1.5s) BF combined with peripapillary VD was 0.841(95% CI: 0.588–0.777, sensitivity:75.9% specifificity:82.9%). Conclusions: 3D-pcASL and OCTA may be effective non-invasive methods to measure ocular blood flow in DR patients and assess the severity of DR.